2011
DOI: 10.1179/1743676111y.0000000001
|View full text |Cite
|
Sign up to set email alerts
|

PTCR effect in donor doped barium titanate: review of compositions, microstructures, processing and properties

Abstract: Barium titanate is widely used in the fabrication of thermistors with a positive temperature coefficient of resistivity (PTCR). The resistivity can increase by several orders of magnitude near the phase transition temperature (Tc) for the ferroelectric tetragonal to the paraelectric cubic phase transformation. There is general agreement that the anomaly in the change of electrical resistivity of donor-doped BaTiO3 around Tc is due to the grain boundary effect. The Heywang-Jonker model and other mechanisms invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(39 citation statements)
references
References 174 publications
0
38
0
1
Order By: Relevance
“…To adjust the electrical characteristics of BaTiO 3 -based ceramic materials, especially to improve their insulating properties, some transition metal elements such as Mn, sometimes accompanied with non-transition metal doping elements, are often added to BaTiO 3 13456. However, adding a small amount of Mn to BaTiO 3 lowers its ferroelectric transition temperature (Curie temperature; T C )7.…”
mentioning
confidence: 99%
“…To adjust the electrical characteristics of BaTiO 3 -based ceramic materials, especially to improve their insulating properties, some transition metal elements such as Mn, sometimes accompanied with non-transition metal doping elements, are often added to BaTiO 3 13456. However, adding a small amount of Mn to BaTiO 3 lowers its ferroelectric transition temperature (Curie temperature; T C )7.…”
mentioning
confidence: 99%
“…The sintered density was affected by the doping level and sintering temperature and will be reported elsewhere . Kuwabara found that the magnitude of the PTCR jump reaches a maximum at an optimum sintered density (≈75%–85% of theoretical density) and then decreases with increasing density. This effect has also been reported in another paper in which samples with low porosity have poor PTCR resistivity jump at T c .…”
Section: Resultsmentioning
confidence: 99%
“…Исследование керамики титаната бариястронция (BST) с примесью редкоземельных элементов привлекает пристальное внимание исследователей в течение многих лет [1][2][3][4]. Интерес вызван тем, что выше температуры Кюри наблюдается резкое увеличение сопротивления образцов т. е. имеет место эффект положительного температурного коэффициента сопротивления (ПТКС), что обеспечивает возможность широкого прикладного использования.…”
Section: Introductionunclassified